Technological Evaluation of Binder Type and Percentage on the Calorific Value and Combustion Rate of Tobacco Stem Briquettes - Mustilan; Dwi Pangga; Sukainil Ahzan; Habibi; Hanandita Veda Saphira (Journal of Innovative Technology and Sustainability Education, 2025)
Objective: This study aims to determine the effect of binder type and percentage on tobacco stem briquettes' calorific value and combustion rate. It also seeks to integrate sensor-based technology to enhance the accuracy of thermal performance measurements, aligning with sustainable energy research and innovation. Method: The research employs an experimental method conducted in three main stages: material preparation, briquette production, and performance testing. The briquettes were made from Tobacco Stem Charcoal (TSC) combined with two types of binders—Tapioca Flour Binder (TFB) and Glutinous Rice Flour Binder (GRFB)—at varying percentages (10%, 12.5%, and 15%). Combustion rate and calorific value were measured using a combination of manual testing and digital sensors (e.g., thermocouples and data loggers), allowing for real-time monitoring and accurate thermal profiling. Results: The results showed that increasing the binder percentage led to a higher calorific value and a lower combustion rate. Calorific values for TFB reached up to 11,844.89 cal, while GRFB reached 10,038 cal. In contrast, TFB's combustion rate decreased from 0.5569 g/min to 0.3826 g/min as the binder percentage increased. Sensor-based measurements confirmed the thermal performance patterns and provided more detailed combustion dynamics data. Novelty: This study contributes to optimizing bio-briquette formulation using agricultural waste and introduces digital sensor technology into the testing process. Integrating technological tools allows for enhanced measurement precision, making this approach a novel contribution to environmentally friendly energy solutions and applied physics education.